"I was yelled at, intimidated and treated unfairly": Nursing students' experiences of being bullied in clinical and academic settings. Issue 5 (8th January 2018) - Courtney‐Pratt, Helen; Pich, Jacqueline; Levett‐Jones, Tracy; Moxey, Annette
Abstract : Aims and objectives: To present findings from a study that explored nursing students' experiences of bullying in clinical and academic settings, the strategies used to negotiate bullying and recommendations for empowering future students. Background: Nursing students are identified as a group who are at particular risk of bullying. Numerous studies have examined students' experiences of bullying in clinical contexts by qualified nurses; however, there has been far less attention to the bullying that occurs in academic settings where the perpetrators are university staff and other students. Design: The qualitative findings presented in this paper form one component of a mixed‐methods, multisite study that examined the nature and extent of bullying in one cohort of nursing students. Methods: A convenience sample of 29 first‐, second‐ and third‐year undergraduate nursing students from one semimetropolitan Australian university was recruited for semistructured interviews in 2014. Interview data were analysed using NVivo. Findings: Participants described multiple examples of bullying occurring in both clinical and academic settings. Perpetrators included clinicians, facilitators, academics and fellow students. Bullying ranged from incivility to physical attacks. The impact of the bullying was profound; it caused many of the participants to feel anxious and distressed, it undermined their confidence and perception of competence, and it often led them to question their career choice. Strategies described by participants to cope with or manage the bullying included avoidance, trying to "just survive" and seeking support from trusted academic staff, family and friends. No episodes of bullying were formally reported. Conclusion: Bullying remains a pervasive phenomenon occurring in both clinical and academic settings. Students are, in many respects, a vulnerable and disempowered population who often fear the consequences of making a formal complaint. Thus, reporting structures and support strategies need to be re‐examined, and resilience training is imperative. Relevance to clinical practice: Bullying remains a continuing concern in undergraduate nursing degrees. Efforts must be made in clinical and academic settings to heed the advice of undergraduates using broader strategies to address the issues.